PRELIMINARY RESULTS OF INTEGRATED FERTILIZATION WITH GREEN MANURE AND MINERAL FERTILIZERS ON MAIZE YIELD - Ionel Alin GHIORGHE; Adrian TUREK-RAHOVEANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Maize (Zea mays L.) is an essential crop worldwide, and the application of fertilizers is a vital management strategy that significantly enhances its yield. The objective of this investigation was to assess the impact of green manure and mineral fertilization on the yield of maize. The experiments were conducted in an experimental field at Agricultural Research and Development Station Braila during the first decade of September 2021 to the second decade of October 2022. A bifactorial experiment was carried out based on the formula A × B, where A represents the green manure crops (a1– control – without green manure crop; a2- winter pea (Pisum sativum L. var. arvense); a3- white mustard (Sinapis alba L.); a4- winter rye (Secale cereale L.); a5- white mustard (Sinapis alba L) + rapeseed (Brassica napus L.); a6- rapeseed (Brassica napus L.) and B represents the mineral fertilization (b1– N0 unfertilized; b2- N60 (60 kg/ ha of N); b3- N90 (90 kg/ ha of N); b4- N120 (120 kg/ ha of N)). The results of this study show the benefits of integrated fertilization with green manure and mineral fertilizer. Maize grain yield was found to be enhanced by using green manure crops.